Partial Discharge Detection Beyond the Frequency Ranges of IEC 60270 - Asawin Rajakrom; Chayapitch Cheechang; Prechapol Laochu; Phethai Nimsanong; Peerawut Yutthagowiht (My University, 2024)
Due to the high background noise encountered during on-site partial discharge (PD) detection of power cables, calibrating PD detection systems at low PD levels becomes challenging, resulting in low sensitivity of PD detection systems. Achieving a 1-nC PD charge within the frequency range recommended by IEC 60270, which is lower than 1 MHz, is often difficult in practice. This paper presents an analysis of PD pulse currents in the frequency domain and proposes an alternative approach for PD detection during on-site testing of power cables. In the proposed method, the center frequency for PD detection is shifted to frequencies exceeding one megahertz, which lies outside the recommended frequency ranges of IEC 60270. Typically, the center frequency falls within the range of 1.5 MHz to 2.5 MHz, with a frequency bandwidth of several hundred kilohertz. By utilizing such frequency ranges, the signal-to-noise ratio of the PD pulse current significantly increases compared to the standard approach. Despite falling outside the standard-recommended frequency ranges, this adjustment allows for calibration using a 50-pC PD charge.
Keywords: High voltage insulation and dielectric phenomena; Smart Grid Security and Resilience; Smart Grid Energy Management